How the policy environment influences value chain linkages: a comparative study of cocoa and pineapple in Ghana - Seth Awuku Manteaw; Jonathan Nicholas Anaglo; Seth Dankyi Boateng; Benjamin Yao Folitse (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
This paper takes its point of departure from the school of thought that linkages in agricultural commodity value chains may hold the key to making actors in the chain innovative. Ghana's agricultural export sector is characterized by two main types of export: traditional and non-traditional. The traditional agricultural export sector is driven largely by the cocoa industry, while the pineapple industry represents one of the leading commodity industries in the non-traditional export sector. Using a multiple case study methodology, the paper seeks to examine how the policy environment could strengthen value chain linkages and make activities in the value chains more competitive. The study was derived from interactions with actors in the cocoa and pineapple value chains, namely input suppliers, producers, buyers, processors and some support services providers and regulatory agencies. The intention was to assemble their perceptions as interpreted in their own settings. The study showed how the existing policy on research, extension and marketing had encouraged better linkages horizontally and vertically among actors in the pineapple value chain. On the other hand, the policy underpinned by a public sector leadership in the cocoa value chain, had lowered the motivation for stronger linkages in the cocoa value chain. In terms of policy implication, the study makes a strong case for more participation of private sector actors as it is more likely to expand the platform for more interactive learning among actors for their mutual benefit.